Acupuncture Effect and Mechanism for Treating Pain in Patients With Parkinson's Disease - Yu, Shao-Wen; Lin, Sung-Han; Tsai, Chih-Chien; Chaudhuri, Kallol Ray; Huang, Yu-Chieh; Chen, Yu-Sheng; Yeh, Bo-Yan; Wu, Yih-Ru; Wang, Jiun-Jie (Frontiers in Neurology, 2019)
Non-motor symptoms of Parkinson's disease (PD) have been receiving increasing attention. Approximately half of patients with PD have experience PD-related pain. We investigated the effect and mechanism of acupuncture in patients with PD who have pain. PD patients with pain were divided into acupuncture group and control group. Nine patients completed acupuncture treatment; seven patients who received only an analgesic agent underwent resting-state functional magnetic resonance imaging (rs-fMRI) twice. fMRI was performed to evaluate the functional connectivity of the brain regions. After treatment, a decrease in total scores on the King's Parkinson's Disease Pain Scale (KPPS) and Unified Parkinson's Disease Rating Scale was observed in the acupuncture group (−46.2 and −21.6%, respectively). In the acupuncture group, increased connectivity was observed in four connections, one in the left hemisphere between the middle temporal gyrus (MTG) and precentral gyrus, and three in the right hemisphere between the postcentral gyrus and precentral gyrus, supramarginal gyrus and precentral gyrus, and MTG and insular cortex. A significant correlation was noted between the changes in functional connectivity and KPPS. The involved connection was between the left middle frontal gyrus and the right precentral gyrus (R = −0.698, P = 0.037). Acupuncture could relieve pain in PD patients by modulating brain regions related to both sensory-discriminative and emotional aspects. The present study might increase the confidence of users that acupuncture is an effective and safe analgesic tool that can relieve PD-related pain.